The Impact of Covid-19 on the Summary Procedure of Indecopi Lambayeque 2020-2023 - Ms. Vanessa Huaccha Vidaurre; Dr. Erik Obiol Anaya (Kurdish Studies, 2024)
The purpose of this article is to show a preview of the panorama that is observed in the summary procedure for consumer protection from Lambayeque during the period 2020 to March 2023, as a consequence of Covid-19.For this, it has been considered important to define the terms consumer and supplier, as market agents; likewise, provide the scope of the summary procedure and identify the most denounced economic sector during the indicated period and the conduct with the greatest concurrence to be questioned; and thus determine the impact of the declaration of the State of Emergency by Covid-19 on consumer issues.In the investigation carried out, it has been observed that during the period 2020 to March 2023, 3,512 administrative complaints were filed before the Indecopi Lambayeque Summary Procedure; of which, 1,510 correspond to the banking and financial sector; also identifying that the conduct referring to unrecognized operations in said economic sector turned out to be the infringing act with the greatest questioning, while 839 complaints were filed that revolved around said matter; This allows us to determine that the Covid-19 has generated an impact on the protection of the Lambayeque consumer in the summary procedure of Indecopi.